Cyclometalated Iridium Complex-Based Label-Free Photoelectrochemical Biosensor for DNA Detection by Hybridization Chain Reaction Amplification - Li, Chunxiang; Wang, Hongyang; Shen, Jing; Tang, Bo (Analytical chemistry (Washington), 2015)
Photoactive material is the most crucial factor which intimately determines analytical performances of the photoelectrochemical sensor. On the basis of the high affinity of dipyrido [3,2-a:2′,3′-c] phenazine (dppz) with DNA helix, a novel photoactive intercalator, [(ppy)2Ir(dppz)]+PF6 –(ppy = 2-phenylpyridine and dppz = dipyrido [3,2-a:2′,3′-c] phenazine) was prepared and characterized by UV–vis absorption spectroscopy, fluorescence spectroscopy, and cyclic voltammetry. The photoelectrochemical properties of the as-prepared iridium(III) complex immobilized on the ITO electrode was investigated. Either cathodic or anodic photocurrent generation can be observed when triethanolamine (TEOA) or dissolved O2 is used as a sacrificial electron donor/acceptor, respectively. The probable photocurrent-generation mechanisms are speculated. A highly sensitive iridium(III) complex-based photoelectrochemical sensor was proposed for DNA detection via hybridization chain reaction (HCR) signal amplification. Under optimal conditions, the biosensor was found to be linearly proportional to the logarithm of target DNA concentration in the range from 0.025 to 100 pmol L–1 with a detection limit of 9.0 fmol L–1 (3σ). Moreover, the proposed sensor displayed high selectivity and good reproducibility, demonstrating efficient and stable photoelectric conversion ability of the Ir(III) complex.